Relationship between the incidence of placenta previa and the characteristics of pregnant women in Lhokseumawe City - Maulina, Nora; Iqbal, Teuku Yudi; Lubis, Rojulan Ilham (Fakultas Kedokteran Universitas Malikussaleh, 2024)
Abnormalities in the location of the placenta, which is in the lower part of the uterus, which can cover part or all of the opening of the birth canal, are known as placenta previa. This can cause critical bleeding in pregnant women in Indonesia. There are several risk factors such as age, parity, cesarean section surgery history, education history, employment history, residence, and cultural background. The purpose of this study was to determine the relationship between the incidence of placenta previa with the characteristics of pregnant women in the city of Lhokseumawe. This research was conducted at RSIA Abby Lhokseumawe city. This research method is observational analytic with a cross-sectional research design. The sampling technique of this study used the total sampling technique with a total sample of 41 samples. The entire process of information processing and analysis uses SPSS.26. The results of this study obtained the following patient characteristics: age 17-35 years (53.7%), age >35 years (46.3%), nulipara (19.5%), primipara (29.3%), sekundipara (24.4%), multipara (26.8%), had experienced cesaria section surgery (39%), and had never had cesaria section surgery (61%). The results of statistical tests found a relationship between age and parity (p = 0.001), number relationship between age and cesaria section surgery history (p = 0.279), and a relationship was found between parity and cesaria section surgery history (p = 0.018). The conclusion of this study is that the majority of pregnant women diagnosed with placenta previa in the city of Lhokseumawe are pregnant women with low risk factors